Assessing the Role and Future of the Tax Court Post-MK Decision No. 26PUU-XXI2023 - Syafwar, Robi; Marwenny, Elwidarifa; Telaumbanua, Friderika Friska (Jurnal Ilmiah Ekotrans & Erudisi, 2024)
Taxation, as a fundamental component of the system of cooperation, serves as a financial resource to underpin governmental financing and expenditure while also acting as an instrument for the regulation of social and economic policies aimed at promoting equitable welfare. The process of tax collection occasionally engenders inequities for taxpayers; consequently, Law 14 of 2002 instituted the Tax Court as an autonomous judicial entity designated for the adjudication of tax-related disputes. Notwithstanding its establishment, the Tax Court encounters significant challenges, notably the dualism of authority wherein the Supreme Court provides technical guidance. At the same time, the Ministry of Finance oversees organizational, administrative, and financial directives. In the Constitutional Court's Decision (MK) Number 26/PUU-XXI/2023, the regulation pertaining to the oversight of the Tax Court was deemed inconsistent with Article 24, paragraphs (1) and (2) of the 1945 Constitution, prompting the Constitutional Court to impose a deadline of December 31, 2026, for the consolidation of the Tax Court's guidance authority under the auspices of the Supreme Court. Consequently, this research endeavours to scrutinize the role and prospective trajectory of the Tax Court alongside the measures necessary to effectuate the transfer of guidance authority in alignment with constitutional mandates. Hence, the author has entitled this study "Measuring the Role and Future of the Tax Court after the Constitutional Court Decision Number 26/PUU-XXI/2023." The questions posed for investigation are: What is the Role and Position of the Tax Court as delineated by the Tax Court Law, and what is the Role and Future of the Tax Court subsequent to the Constitutional Court Decision (Number 26/PUU-XXI/2023)? To address these inquiries, the author employs a qualitative writing methodology complemented by a normative legal perspective.